Results of CHOP chemotherapy for diffuse large B-cell lymphoma - Hallack Neto,A.E. (2006)
Patients with diffuse large B-cell lymphoma treated in a University Hospital were studied from 1990 to 2001. Two treatment regimens were used: ProMACE-CytaBOM and then, from November 1996 on, the CHOP regimen. Complete remission (CR), disease-free survival (DFS), and overall survival (OS) rates were determined. Primary refractory patients and relapsed patients were also assessed. A total of 111 patients under 60 years of age were assessed and ranked according to the international prognostic index adjusted to age. Twenty (18%) of them were classified as low risk, 40 (36%) as intermediate risk, 33 (29.7%) as high intermediate risk, and 18 (16.3%) as high risk. Over a five-year period, OS and DFS rates were 71 and 59%, respectively, for all patients. For the same time period, OS and DFS rates were 72.8 and 61.3%, respectively, for 77 patients treated with CHOP chemotherapy and 71.3 and 60% for patients treated with the ProMACE-CytaBOM protocol. There was no significant difference in OS or DFS between the two groups. Eleven of 50 refractory and relapsed patients were consolidated with high doses of chemotherapy. Three received allogenic and 8 autologous bone marrow transplantation. For the latter, CR was 62.5% and mean OS was 41.1 months. The clinical behavior, CR, DFS, and OS of the present patients were similar to those reported in the literature. We conclude that both the CHOP and ProMACE-CytaBOM protocols can be used to treat diffuse large B-cell lymphoma patients, although the CHOP protocol is preferable because of its lower cost and lower toxicity.